Concerto for Choir in Memory of Kara Karaiev - Mamedova, Leila (Vìsnik Kiïvsʹkogo nacìonalʹnogo unìversitetu kulʹturi ì mistectv. Serìâ: Muzične mistectvo, 2018)
The purpose of the study is to identify the characteristics of choral writing Faik Nagiiev on example of the bright and original composition "Concerto for choir in memory of K. Karaiev”. This large-scale, in three parts, piece for choir a cappella choir was for the first time the subject of serious scientific studies.  The various research methods were used, as follows empirical to identify innovative sonorous techniques in musical material and theoretical for in-depth analysis of national peculiarities of Azerbaijan composers’ school in its traditional and innovative aspects, as from the performing side, and from the point of view of theoretical analysis, because both of these research methods are closely interrelated. In addition the method of cognitive-event interpretation of complex and multilayered musical material of composition was widely used. The scientific novelty of the research is determined, firstly by the deep study of modern composers’ choral music in general and F.Nagiiev in particular. Also carefully studied features the composer's choral writing, traces the evolution of the development of choral genre in Azerbaijan, carried out a comparative analysis of the development of the modern world of choral music and choral music in the country. “Concerto for choir in memory of K. Karaiev” is a kind of Requiem in memory of the great teacher, sorrow and pain of the loss which the composer F. Nagiiev expressed in genre of choir concert a cappella. Having thoroughly studied the composition we came to the conclusion that the current state of Azerbaijan composers’ school is on the high level of its development. In addition, the possibilities of performing groups in the country are also weight and substantial. Innovative choral writing is evident in the use of expressiveness multiple tools of various abilities of performer voice box (whisper, speech recitation, glissando using, lamentation and coronach etc.).